Usability Evaluation of the Restaurant Finder Application Using Inspection and Inquiry Methods - Putri Ambarwati; Metty Mustikasari (Jurnal Sistem Informasi, 2021)
Restaurant Finder application is a mobile application that helps users to find restaurants according to their requirements. One of the most well-known and widely used restaurant finder apps is Zomato. Zomato ranks first in the food and delivery category websites from around the world. But, the number of users of a product or application certainly does not guarantee the satisfaction of the user experience of apps. A system that is poorly designed will make it difficult for users, which results in the system being rarely or misused so that the costs to the organization become high and dangerous to the reputation of the company. The purpose of this study was to evaluate the usability of the restaurant finder application using inspection and inquiry methods. Inspection method using the Enhanced Cognitive Walkthrough method, and for inquiry methods using the User Experience Questionnaire method and the System Usability Scale. The inspection method results identified 7 serious problems. Recommendations for improvement based on inspection methods are focused on login tasks, reviews, and food promo information. The inquiry methods results identified 5 aspects that needed improvement. The five aspects consist of novelty, stimulation, learnability, consistency, complexity.